Trans-cerebral HCO3− and PCO2 exchange during acute respiratory acidosis and exercise-induced metabolic acidosis in humans. Issue 4 (April 2022) - Caldwell, Hannah G; Hoiland, Ryan L; Smith, Kurt J; Brassard, Patrice; Bain, Anthony R; Tymko, Michael M; Howe, Connor A; Carr, Jay MJR; Stacey, Benjamin S; Bailey, Damian M; Drapeau, Audrey; Sekhon, Mypinder S; et al.
This study investigated trans-cerebral internal jugular venous-arterial bicarbonate ([HCO3 − ]) and carbon dioxide tension (PCO2 ) exchange utilizing two separate interventions to induce acidosis: 1) acute respiratory acidosis via elevations in arterial PCO2 (PaCO2 ) (n = 39); and 2) metabolic acidosis via incremental cycling exercise to exhaustion (n = 24). During respiratory acidosis, arterial [HCO3 − ] increased by 0.15 ± 0.05 mmol ⋅ l −1 per mmHg elevation in PaCO2 across a wide physiological range (35 to 60 mmHg PaCO2 ; P < 0.001). The narrowing of the venous-arterial [HCO3 − ] and PCO2 differences with respiratory acidosis were both related to the hypercapnia-induced elevations in cerebral blood flow (CBF) (both P < 0.001; subset n = 27); thus, trans-cerebral [HCO3 − ] exchange (CBF × venous-arterial [HCO3 − ] difference) was reduced indicating a shift from net release toward net uptake of [HCO3 − ] (P = 0.004). Arterial [HCO3 − ] was reduced by −0.48 ± 0.15 mmol ⋅ l −1 per nmol ⋅ l −1 increase in arterial [H + ] with exercise-induced acidosis (P < 0.001). There was no relationship between the venous-arterial [HCO3 − ] difference and arterial [H + ] with exercise-induced acidosis or CBF; therefore, trans-cerebral [HCO3 − ] exchange was unaltered throughout exercise when indexed against arterial [H + ] or pH (P = 0.933 and P = 0.896, respectively). These results indicate that increases and decreases in systemic [HCO3 − ] – during acute respiratory/exercise-induced metabolic acidosis, respectively – differentially affect cerebrovascular acid-base balance (via trans-cerebral [HCO3 − ] exchange).